Temporal and Spatial Trends of Leptospirosis Cases in Sri Lanka - Sanjeewani, R.M.S.S. (My University, 2017)
Leptospirosis is most common in tropical and subtropical areas and becoming an emerging infectious disease in Sri Lanka too. Leptospirosis is a bacterial disease which is caused by bacteria of the genus Leptospira. Leptospirosis is intensified by high humidity and heavy rainfall because of widespread contamination by rodent urine in flood water. Currently flood events are being reported frequently and it is timely important to studytrends of Leptospirosis cases in Sri Lanka to be considered for planning prevention and control activities. This study aims to identify temporal and spatial trends of Leptospirosis distribution in Sri Lanka. ArcGIS 10.3 is used to map the spatial distribution of leptospirosis cases in Sri Lanka and basic statistical analysis is further applied to derive spatial and temporal trends and patterns of leptospirosis. Accordingly leptospirosis is widely recorded in wet zonal districts including Colombo, Kalurata, Ratnapura, Kegalle, Gampaha, Matara and Galle with highlighted exception in Kurunegala and Anuradhapura despite of wet zonal districts.This study further identifies that the dry zonal districts including Moneragala, Hambanthoota and Polonnaruwa are also under the emerging threat of leptospirosis depictingfurther micro-geographic variation of leptospirosis other than Kurunegala and Anuradhapura. Hence these areas can also be prioritize when planning local level leptospirosis control and prevention strategies.
Keywords: Leptospirosis, GIS, temporal, spatial, trends